Measuring Effectiveness of Adult Literacy Program in India - Joshi, S. B.; Bohra, N. S. (Journal of Graphic Era University, 2023)
<span dir="ltr" style="left: calc(var(–scale-factor)*72.02px); top: calc(var(–scale-factor)*291.05px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.965539);" role="presentation">The <span dir="ltr" style="left: calc(var(–scale-factor)*90.98px); top: calc(var(–scale-factor)*291.05px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.909409);" role="presentation">study <span dir="ltr" style="left: calc(var(–scale-factor)*115.82px); top: calc(var(–scale-factor)*291.05px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.871256);" role="presentation">assesses the problems <span dir="ltr" style="left: calc(var(–scale-factor)*208.01px); top: calc(var(–scale-factor)*291.05px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.959089);" role="presentation">of Adult Literacy Programs <span dir="ltr" style="left: calc(var(–scale-factor)*324.07px); top: calc(var(–scale-factor)*291.05px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(1.00578);" role="presentation">(ALP) <span dir="ltr" style="left: calc(var(–scale-factor)*353.11px); top: calc(var(–scale-factor)*291.05px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.981116);" role="presentation">in India <span dir="ltr" style="left: calc(var(–scale-factor)*388.15px); top: calc(var(–scale-factor)*291.05px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.920382);" role="presentation">with special reference to Sakshar <span dir="ltr" style="left: calc(var(–scale-factor)*72.02px); top: calc(var(–scale-factor)*304.25px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.919251);" role="presentation">Bharat Program in Uttarakhand. T<span dir="ltr" style="left: calc(var(–scale-factor)*209.81px); top: calc(var(–scale-factor)*304.25px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.843162);" role="presentation">he <span dir="ltr" style="left: calc(var(–scale-factor)*221.81px); top: calc(var(–scale-factor)*304.25px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.874201);" role="presentation">response analysis <span dir="ltr" style="left: calc(var(–scale-factor)*294.17px); top: calc(var(–scale-factor)*304.25px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(1.00562);" role="presentation">of <span dir="ltr" style="left: calc(var(–scale-factor)*305.21px); top: calc(var(–scale-factor)*304.25px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.952939);" role="presentation">two key <span dir="ltr" style="left: calc(var(–scale-factor)*340.03px); top: calc(var(–scale-factor)*304.25px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.883844);" role="presentation">stakeholders<span dir="ltr" style="left: calc(var(–scale-factor)*389.95px); top: calc(var(–scale-factor)*304.25px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.898292);" role="presentation">, one as a learner (those to whom <span dir="ltr" style="left: calc(var(–scale-factor)*72.02px); top: calc(var(–scale-factor)*317.57px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.897874);" role="presentation">this program is made for) and other as <span dir="ltr" style="left: calc(var(–scale-factor)*226.37px); top: calc(var(–scale-factor)*317.57px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.921935);" role="presentation">functionaries <span dir="ltr" style="left: calc(var(–scale-factor)*280.85px); top: calc(var(–scale-factor)*317.57px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.907947);" role="presentation">(those by whom this program is executed) <span dir="ltr" style="left: calc(var(–scale-factor)*451.42px); top: calc(var(–scale-factor)*317.57px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.895284);" role="presentation">have been utilised <span dir="ltr" style="left: calc(var(–scale-factor)*72.02px); top: calc(var(–scale-factor)*330.77px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.951085);" role="presentation">for the research work. <span dir="ltr" style="left: calc(var(–scale-factor)*167.42px); top: calc(var(–scale-factor)*330.77px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.943521);" role="presentation">Data have been analysed through statistical techniques like Karl <span dir="ltr" style="left: calc(var(–scale-factor)*437.95px); top: calc(var(–scale-factor)*330.77px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.931268);" role="presentation">Pearson’s coefficient <span dir="ltr" style="left: calc(var(–scale-factor)*72.02px); top: calc(var(–scale-factor)*343.97px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.933764);" role="presentation">correlation and ANOVA computed through SPSS. <span dir="ltr" style="left: calc(var(–scale-factor)*278.81px); top: calc(var(–scale-factor)*343.97px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.92773);" role="presentation">Findings <span dir="ltr" style="left: calc(var(–scale-factor)*316.87px); top: calc(var(–scale-factor)*343.97px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.919639);" role="presentation">of the research work <span dir="ltr" style="left: calc(var(–scale-factor)*402.91px); top: calc(var(–scale-factor)*343.97px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.909503);" role="presentation">reveal that <span dir="ltr" style="left: calc(var(–scale-factor)*448.30px); top: calc(var(–scale-factor)*343.97px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.913628);" role="presentation">the contents of the <span dir="ltr" style="left: calc(var(–scale-factor)*72.02px); top: calc(var(–scale-factor)*357.17px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.916695);" role="presentation">program are not linked to the learner’s economic activities and infrastructure is not satisfactory.